(untitled) (Kinesiology, 2022)
This study aimed to analyze the isolated and combined effects of non-modifiable factors on adolescents’ physical fitness. This cross-sectional, descriptive study involved 1475 adolescents, aged 12 to 19 years, of whom 721 were girls, from four public schools in southern Spain. Physical activity, birth weight and breastfeeding time, and physical fitness were assessed. To calculate the 2D:4D ratio, three separate measurements of the length of the index finger (2D) and ring finger (4D) of both hands were taken. Results show no differences in the intake of breast milk nor its prediction power for physical fitness. Birth weight was related to horizontal jump and manual dynamometry results, while the 2D:4D ratio was not significant in the linear regression models. The non-modifiable factors studied in relation to physical activity practically ceased to be significant when variables such as sex, body mass index and physical activity practice were introduced into the models. Key words: physical fitness, adolescents, birth weight, breastfeeding